Optimizing Teachers’ Potential as Youtubers to Face Merdeka Belajar - Masni Masni; Maya Agustina; Khairuddin Hasan (STAI Hubbulwathan Duri, 2024)
The research aims to find out whether YouTuber teachers are able to face Merdeka Belajar, what variations of learning videos are produced by YouTuber teachers and to what extent YouTuber teachers are able to face Merdeka Belajar in Aceh Jaya. The research method uses the Asset Based Community Development method which has five stages, namely Discovery, Dream, Design, Define, and Destiny. The research subjects were 20 teachers who served in madrasas who were determined using purposive sampling techniques. Data collection uses interviews, observation, documentation and focus group discussions. Data analysis uses data reduction, data coding, data verification, and drawing conclusions. The results of the research showed that YouTuber teachers in Aceh Jaya were ready to face Merdeka Belajar. The teachers' willingness could be seen from the competence they had in designing learning videos as a distance learning tool. Distance learning was a form of independent learning. YouTuber teachers were also able to produce attractive learning videos, which were divided into four variations, namely voice note type videos, mixed voice videos, direct type videos, and semi-practical videos. The research results had implications for madrasah policy in Aceh Jaya in increasing the competence of other teachers in producing learning videos.